Sentinel lymph node biopsy and aberrant lymphatic drainage in recurrent breast cancer: Findings likely to change treatment decisions. Issue 7 (25th October 2016) - Karanlik, Hasan; Ozgur, Ilker; Kilic, Berkay; Fathalizadeh, Alisan; Sanli, Yasemin; Onder, Semen; Saip, Pinar; Sen, Fatma; Gulluoglu, Bahadir M.
Abstract : Background and Objectives: It is not clear whether sentinel lymph node biopsy (SLNB) can be applied to patients with a second breast cancer or recurrence occurring at previously treated breast. The purpose of this study was to assess the feasibility of SLNB procedure in patients with recurrent breast cancer. Methods: Patients with non‐metastatic recurrent N0 breast cancer at ipsilateral breast were included. Patients were grouped according to their initial breast, axilla, and overall surgery. Presence of drainage and its pattern as well as SLNB success rate and overall axillary involvement rates were assessed. Findings were compared. Results: Out of 75 patients, mean age was 52.5 years and disease‐free interval was 82 (9–312) months. Lymphatic drainage was successful in 42 (56%) patients. Drainage positivity was more frequent in patients who were previously treated with SLNB (82.6%) than in patients who underwent axillary lymph node dissection (ALND) (44.2%; P  = 0, 002). Aberrant lymphatic drainage was detected in 64.3% of drainage positive patients. Success rate of reoperative SLNB was 92.9%. Adjuvant treatment plan was altered in 12 (16%) patients. In 15 patients, negative SLNB prevented axillary dissection. Conclusions: Reoperative SLNB seems to be technically feasible in N0 recurrent breast cancer patients. It may further avoid unnecessary ALND and lead changes in adjuvant treatment plans. J. Surg. Oncol. 2016;114:796–802 . © 2016 2016 Wiley Periodicals, Inc.